MOA-2016-BLG-227Lb: a massive planet characterized by combining light-curve analysis and Keck AO imaging - Koshimoto, Naoki; Tsapras, Yiannis (Arxiv, 2017)
We report the discovery of a microlensing planet --- MOA-2016-BLG-227Lb --- with a large planet/host mass ratio of \simeq 9 × 10^{-3}$. This event was located near the $K2$ Campaign 9 field that was observed by a large number of telescopes. As a result, the event was in the microlensing survey area of a number of these telescopes, and this enabled good coverage of the planetary light curve signal. High angular resolution adaptive optics images from the Keck telescope reveal excess flux at the position of the source above the flux of the source star, as indicated by the light curve model. This excess flux could be due to the lens star, but it could also be due to a companion to the source or lens star, or even an unrelated star. We consider all these possibilities in a Bayesian analysis in the context of a standard Galactic model. Our analysis indicates that it is unlikely that a large fraction of the excess flux comes from the lens, unless solar type stars are much more likely to host planets of this mass ratio than lower mass stars. We recommend that a method similar to the one developed in this paper be used for other events with high angular resolution follow-up observations when the follow-up observations are insufficient to measure the lens-source relative proper motion.
Gesehen am 19.10.2017